2023
DOI: 10.1002/jez.2705
|View full text |Cite
|
Sign up to set email alerts
|

Blood biochemistry parameters of Broad snouted caiman, Caiman latirostris subjected to stress conditions, appliying micro‐volume techniques

Abstract: Plasma biochemistry values represent a crucial and minimally invasive tool for evaluating nutritional and physiological condition of the animal. Biochemical data provides valuable information in those species exposed to environmental stressors. In this study, we aimed to apply for the first time micro‐volume plasma tests to measured total plasma protein, albumin, and glucose in juvenile Caiman latirostris and to compare our results with other studies reporting crocodilian biochemistry values. We found that cai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Thus, the slow and arrested bone deposition we observed in the juveniles could be related to the low temperatures during winter (average of 12.1°C) in Santa Fé. However, given that Moleón et al (2023) found that temperature had no effect on digestion in C. latirostris , caution that perhaps other factors may also be affecting growth. Curiously, the humerus of a 1‐year‐old C. latirostris studied previously (Mascarenhas‐Junior et al, 2021; Figure 13) did not show growth marks as we observed in our specimens.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, the slow and arrested bone deposition we observed in the juveniles could be related to the low temperatures during winter (average of 12.1°C) in Santa Fé. However, given that Moleón et al (2023) found that temperature had no effect on digestion in C. latirostris , caution that perhaps other factors may also be affecting growth. Curiously, the humerus of a 1‐year‐old C. latirostris studied previously (Mascarenhas‐Junior et al, 2021; Figure 13) did not show growth marks as we observed in our specimens.…”
Section: Discussionmentioning
confidence: 94%